Peran manajemen risiko dalam proses meningkatkan kinerja karyawan - Putra, Muhammad Arvian Rivanda (Maliki Interdisciplinary Journal, 2024)
The purpose of writing this research is to analyze the role of risk management in developing a literature review regarding analysis of the company performance of PT GPS. Methods used in Personnel Management This research is a literature review that replicates the findings. This scientific article was written using qualitative methods and a literature search using the latest text found in Google Scholar and Mendeley searches. Based on research, it is concluded that risk management plays a role in the company’s operations at PT GPS. Therefore, risk management plays an important role in the company’s business activities. Risk management is one of the terms used in management. There are facilities that can be found within the company.